Sovereign debt in the 21st century - Kris James Mitchener; Christoph Trebesch (Kiel Institute for the World Economy (IfW), 2022)
How will sovereign debt markets evolve in the 21st century? We survey how the literature has responded to the eurozone debt crisis, placing "lessons learned" in historical perspective. The crisis featured: (i) the return of debt problems to advanced economies; (ii) a bank-sovereign "doom-loop" and the propagation of sovereign risk to households and firms; (iii) roll-over problems and self-fulfilling crisis dynamics; (iv) severe debt distress without outright sovereign defaults; (v) large-scale sovereign bailouts from abroad; and (vi) creditor threats to litigate and hold out in a debt restructuring. Many of these characteristics were already present in historical debt crises and are likely to remain relevant in the future. Looking forward, our survey points to a growing role of sovereign-bank linkages, legal risks, domestic debt and default, and of official creditors, due to new lenders such as China as well as the increasing dominance of central banks in global debt markets. Questions of debt sustainability and default will remain acute in both developing and advanced economies.
Keywords: F30; F34; G12; G15; N10; N20; 330; Internationale Staatsschulden; Wirtschaftsprognose; Welt